Delayed Onset Vascular Stiffening Induced by Eccentric Resistance Exercise and Downhill Running. Issue 4 (July 2017) - Lin, Hsin-Fu; Chou, Chun-Chung; Cheng, Hao-Min; Tanaka, Hirofumi
Abstract : Objectives: Eccentric exercise induces muscle stiffening and soreness as well as unfavorable changes in macrovascular function. We tested the hypothesis that systemic eccentric exercise could evoke greater arterial stiffening than local eccentric resistance exercise. Design and Intervention: Twenty healthy young men were randomly assigned into either the downhill running (DR) and the eccentric resistance exercise (RE) group followed by a crossover design with an exercise and sham control trial. Main Outcome Measures: Carotid–femoral pulse wave velocity (cfPWV), central hemodynamic measures, and biomarkers were obtained. Results: Muscle soreness and plasma creatine kinase concentrations increased similarly after exercise in both groups. The cfPWV increased significantly at 48 hours post-exercise in both groups and remained elevated at 72 hours in DR. C-reactive protein (CRP) was elevated at 24 and 48 hours in DR, and 48 hours in RE. The increases in cfPWV were associated with the corresponding elevations in CRP in DR (r = 0.70, P < 0.05). There were no changes in arterial wave reflection measures. Conclusions: Both systemic and localized eccentric exercise modes induced delayed onset vascular stiffening with more prolonged changes observed in downhill running. The effect on arterial stiffening was associated, at least in part, with systemic inflammatory responses.